2000
DOI: 10.1159/000027772
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Salivary Gland Tumors in Quito, Ecuador

Abstract: Objectives: Malignant salivary gland tumors (MSGT) are uncommon. Age-standardized incidence rates are 0.5 and 0.3 per 100,000 in Quito, Ecuador; and 1.0 and 0.7 per 100,000 in the USA (SEER Program), for males and females, respectively. The goal of this study was to review a 16-year experience of a major general hospital in the treatment of these lesions. Patients and Methods: From 1982 to 1998, 308 salivary gland tumors were surgically treated at the Hospital ‘Carlos Andrade Marin’ of the Ecuadorian Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…These results are consistent with results obtained in several studies. [ 8 30 36 37 38 ] However, some studies have reported mucoepidermoid carcinoma to be the most common tumor. [ 12 15 18 29 39 40 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with results obtained in several studies. [ 8 30 36 37 38 ] However, some studies have reported mucoepidermoid carcinoma to be the most common tumor. [ 12 15 18 29 39 40 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…They present an annual incidence ranging from 0.5 to 7 cases per 100,000 individuals [5][6][7][8] , comprehending less than 9% of head and neck neoplasms 3,[9][10][11] . The tumors affecting these glands are of great relevance, considering the variations in clinical, histological and biological behavior [12][13][14] . The prognosis of salivary gland tumors correlates directly with the clinical stage of the disease; early diagnosis contributes for a better prognosis 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland tumors are uncommon, corresponding to approximately 3% to 10% of neoplasms of the head and neck region 1,2 . Incidence rates of malignant salivary gland tumors range from 0.5 to 1.2 cases per 100,000 inhabitants per year 3,4 . These tumors occur mainly in the parotid gland, but the submandibular gland, minor salivary gland (15% of all salivary gland neoplasms), and sublingual gland can be affected too 1 .…”
Section: Introductionmentioning
confidence: 99%